2021
DOI: 10.1016/j.bone.2021.116146
|View full text |Cite
|
Sign up to set email alerts
|

Osteophyte size and location on hip DXA scans are associated with hip pain: Findings from a cross sectional study in UK Biobank

Abstract: Objective It remains unclear how the different features of radiographic hip osteoarthritis (rHOA) contribute to hip pain. We examined the relationship between rHOA, including its individual components, and hip pain using a novel dual-energy x-ray absorptiometry (DXA)-based method. Methods Hip DXAs were obtained from UK Biobank. A novel automated method obtained minimum joint space width (mJSW) from points placed around the femoral head and acetabulum. Osteophyte areas a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…A machine learning Random Forest-based algorithm, which was initially trained on ∼7000 manually marked-up images, automatically placed 85 outline points around the left femoral head and acetabulum [ 11 , 20 , 21 ] ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A machine learning Random Forest-based algorithm, which was initially trained on ∼7000 manually marked-up images, automatically placed 85 outline points around the left femoral head and acetabulum [ 11 , 20 , 21 ] ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This likely reflects not only ambiguity and subjectivity of scoring, but also limitations in how these scores are derived. For example, whereas KL and Croft grading both give equal weighting to joint space narrowing (JSN) and osteophytes, yet where these have been examined individually, osteophyte severity shows a stronger association with hip pain than does JSN [ 10 , 11 ]. On top of this, when examined in isolation in a large systematic review, minimum joint space width (mJSW), a continuous measure of JSN, showed weak associations with hip symptoms questioning its predominance in these scoring systems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was this wider research programme that guided the sample size selection as large samples are needed for machine learning. The remainder of the training and extension samples (80%) were selected randomly ensuring the sexes were equally weighted 19 . The combined sample is made up of both the training and extension sample.…”
Section: Methodsmentioning
confidence: 99%
“…Dual-energy x-ray absorptiometry (DXA) scans are commonly used to derive measures of bone mineral density, and are increasingly being used to look at hip shape 16 , 17 . In addition, a new generation of hip DXA scanner allows for higher resolution images which has led to the use of DXA scans in detecting radiographic OA for research purposes 18 , 19 . Compared to radiographs, DXA scans involve lower radiation doses and are available from larger population studies, such as the UK Biobank (UKB) enhanced imaging study 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%